Effects of isoflavones on breast density in pre- and post-menopausal women: a systematic review and meta-analysis of randomized controlled trials - Hooper, Lee (Oxford University Press, 2010)
BACKGROUND: Isoflavones from soy and red clover exert modest hormonal effects in women, but the relevance to risk of breast cancer is unclear. The aim of this meta-analysis was to assess the effects of isoflavone-rich foods or supplements on a biomarker of breast cancer risk, women's mammographic density. METHODS: Electronic searches were performed on The Cochrane Library, Medline and EMBASE (to June 2009), and reference lists and trial investigators were consulted to identify further studies. Randomized controlled trials (RCTs) of isoflavone-rich foods or supplements versus placebo with a duration of at least 6 months were included in our analysis. Inclusion/exclusion, data extraction and validity assessment were carried out independently in duplicate, and meta-analysis used to pool study results. Subgrouping, sensitivity analysis, assessment of heterogeneity and funnel plots were used to interpret the results. RESULTS: Eight RCTs (1287 women) compared isoflavones with placebo for between 6 months and 3 years. Meta-analysis suggested no overall effect of dietary isoflavones on breast density in all women combined [mean difference (MD) 0.69%, 95% confidence interval (CI) −0.78 to 2.17] or post-menopausal women (MD −1.10%, 95% CI −3.22 to 1.03). However, there was a modest increase in mammographic density in premenopausal women (MD 1.83%, 95% CI 0.25–3.40) without heterogeneity but this effect was lost in one of three sensitivity analyses. CONCLUSIONS: Isoflavone intake does not alter breast density in post-menopausal women, but may cause a small increase in breast density in premenopausal women. Larger, long-term trials are required to determine if these small effects are clinically relevant.